In silico studies on leishmanicide activity of limonoids and fatty acids from Carapa guianensis Aubl - de Barros, Renilson Castro; Araujo da Costa, Renato; Farias, Suelem Daniella Pinho; de Albuquerque, Kelly Cristina Oliveira; Marinho, Andrey Moacir R.; Campos, Marliane Batista; Marinho, Patrícia Santana Barbosa; Dolabela, Maria Fani (Frontiers in Chemistry, 2024)
The oil of Carapa guianensis showed leishmanicidal activity, with its activity being related to limonoids, but fatty acids are the major constituents of this oil. The present study evaluated the physicochemical, pharmacokinetic, and toxicity profiles of limonoids and fatty acids already identified in the species. Based on these results, 2 limonoids (methyl angosinlate, 6-OH-methyl angosinlate) and 2 fatty acids (arachidic acid; myristic acid) were selected for the prediction of possible targets and molecular docking. Included in this study were: Gedunin, 6α-acetoxygedunin, Methyl angosenlato, 7-deacetoxy-7-oxogedunin, Andirobin, 6-hydroxy-angolensate methyl, 17β-hydroxyazadiradione, 1,2-dihydro-3β-hydroxy-7-deacetoxy-7-oxogedunin, xyllocensin k, 11beta-Hydroxygedunin, 6α,11-11β-diacetoxygedunin, Oleic Acid, Palmitic Acid, Stearic Acid, Arachidic Acid, Myristic Acid, Palmitoleic Acid, Linoleic Acid, Linolenic Acid, and Beenic Acid. Regarding physicochemical aspects, fatty acids violated LogP, and only limonoid 11 violated Lipinski’s rule. A common pharmacokinetic aspect was that all molecules were well absorbed in the intestine and inhibited CYP. All compounds showed toxicity in some model, with fatty acids being mutagenic and carcinogenic, and limonoids not being mutagenic and carcinogenic at least for rats. In in vivo models, fatty acids were less toxic. Molecular dockings were performed on COX-2 steroids (15 and 16) and hypoxia-inducible factor 1 alpha for limonoids (3,6), with this target being essential for the intracellular development of leishmania. Limonoids 3 and 6 appear to be promising as leishmanicidal agents, and fatty acids are promising as wound healers.